Febrile Ordeal: A Case of Human Herpesvirus 8–Induced Hemophagocytic Lymphohistiocytosis in a Cardiac Transplant Patient - Inemesit Akpan; Patrick Berchie; Rajeev Singh; Zola Nlandu (Annals of Internal Medicine: Clinical Cases)
Hemophagocytic lymphohistiocytosis (HLH) occurs due to the proliferation of the mononuclear phagocytic system, resulting in marked hemophagocytosis. The nonspecific clinical and laboratory findings make the diagnosis of HLH a challenge. Here, we present a postcardiac transplant patient with recurrent fever of unknown origin who was found to have HLH induced by human herpesvirus 8 infection. Our patient's nonspecific symptoms made it challenging to arrive at the diagnosis, which delayed management.